Pretrial Decision-Making Matrices: The Role of Risk and Charge Weighting in Risk Assessment–Guided Decisions - Lowder, Evan Marie (Criminal justice and behavior, 2023)
Pretrial risk assessments are used in local pretrial settings to inform release and supervision decisions. Yet, there is little research on the implementation of pretrial risk assessments in practice. We examined the characteristics of pretrial decision-making matrices in a statewide sample of counties using the same risk assessment tool. We procured pretrial decision-making matrices from 29 Indiana counties that had received or were in the process of receiving pretrial certification (88.6% response rate). Using a structured coding protocol, we found matrices shared common features but differed in their structure and available release and supervision options. Matrices weighted index charge information more heavily than risk assessment information, suggesting risk assessments likely explain between 20% and 36% of variability in decisions given typical rates of judicial adherence. Local decision-makers should be aware that structuring matrices to weight charge information more heavily than risk assessment information may limit the risk management potential of these tools.